KAPABILITAS PENDAMPING SOSIAL DALAM PROSES GRADUASI KELUARGA PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN DI KABUPATEN GARUT PROVINSI JAWA BARAT - Helly Ocktilia (Politeknik Kesejahteraan Sosial Bandung, 2024)
AbstractThe research aims to describe the capabilities of PKH companions in the graduation process of Beneficiary Families or Keluarga Penerima Manfaat (KPM) of the Family Hope Program or Program Keluarga Harapan (PKH) by examining individual capability aspects using Mayo's approach (2000), namely: personal capabilities, transfer knowledge, experience, network, and values and attitude. The research design uses a descriptive method with a qualitative approach. The results show that the capabilities of PKH social companions in carrying out their main tasks have brought about changes in the awareness of PKH KPM to undergo graduation. Personal capabilities show a persuasive and humanistic approach from social companions that consciously and without coercion lead KPM to decide to graduate; Transfer knowledge capabilities about graduation significantly determine the awareness and behavior of KPM regarding their potential and the growth of confidence in their ability to be independent; The experience capabilities of social companions have formed pedagogical, personality, social, and professional competence of social companions; The capability to build a network of social companions is carried out through four stages of the process flow: assessment of KPM problems and needs, planning to build a network, implementation of building a network, and evaluation of activities; and values and attitude capabilities are reflected in building similarities between companions and KPM as well as respect for the values held by the community. In conclusion, PKH KPM social companions in Garut District can carry out their duties well in the graduation process of PKH KPM through their capabilities.